CORPORATE SOCIAL RESPONSIBILITY REPORTING: DOES WRITING STYLE MATTER? - Harjoto, Maretno Agus; Jadallah, Jadallah; Laksmana, Indrarini; Lee, W. Eric (International Journal of Accounting & Finance Review, 2021)
This study offers an extension of Harjoto, Laksmana and Lee (2020) by presenting a descriptive comparison of gender differences in writing style, and how they impact the choice of words and the readability of corporate social responsibility (CSR) reports. We examine readability, solidarity, and certainty of CSR reports. We find that female CSR leaders use a writing style that conveys greater solidarity with their audience, thereby making a better connection with the stakeholders. These CSR reports are also more readable than those written by their male counterparts. The attributes of readability and solidarity, but not certainty, are in turn positively related to future CSR performance. In comparison, for CSR reports issued by male signers, we find a writing style that conveys greater certainty, which is in turn positively associated with the firms’ future financial performance. Overall, findings show that writing style of CSR reports is an important issue for both firms and investors to consider. JEL Classification Codes: M4, Q5, Z1.